Cases in strategic management - Grigsby, David W. (Blackwell, 1997)
Harley-Davidson, Inc. The Swatch in 1993. Hoechst-Roussel pharmaceuticals, Inc.: RU 486. The rise and fall of Yugo America, Inc. GM Allison Japan Ltd. Kenhar products, Inc....